Overexpression of Androgen, Oestrogen and Progesterone Receptors in Skin Lesions of Becker's Naevus - Ping Sheng; Yun-Long Cheng; Chuan-Chuan Cai; Ya-Yun Wu; Ge Shi; Ying Zhou; Yi-Ming Fan (Medical Journals Sweden, 2018)
Becker's naevus is androgen-dependent. The aim of this study was to investigate whether oestrogen and progesterone receptors are involved in this disorder. Immunohistochemistry showed that epidermal expression of androgen receptors, oestrogen receptors (α, β) and progesterone receptors was higher in skin lesions of Becker's naevus than in perilesional and control skin. Androgen receptor overexpression was observed in pilosebaceous glands, while oestrogen and progesterone receptor overexpression was seen in hair follicles, but not in sebaceous glands in skin lesions compared with perilesional skin. Reverse transcription PCR and Western blot revealed that levels of androgen, oestrogen and progesterone receptors were generally upregulated in skin lesions compared with perilesional and control skin, and their expression was usually higher in perilesional than in control skin. These results suggest that simultaneous overexpression of androgen, oestrogen and progesterone receptors might be implicated in the pathogenesis of Becker's naevus.